DCE-MRI biomarkers for monitoring an anti-angiogenic triple combination therapy in experimental hypopharynx carcinoma xenografts with immunohistochemical validation. (March 2015) - Sterzik, Alexander; Paprottka, Philipp M; Zengel, Pamela; Hirner, Heidrun; Roßpunt, Svenja; Eschbach, Ralf; Moser, Matthias; Havla, Lukas; Ingrisch, Michael; Mack, Brigitte; Reiser, Maximilian F; Nikolaou, Konstantin; et al.
Background: Novel anti-angiogenic treatments are increasingly complementing established cancer therapy strategies in head and neck tumors. Contrast-enhanced magnetic resonance imaging (MRI) can be applied for early and non-invasive therapy monitoring by non-invasive quantitative assessment of tumor microcirculation as in vivo imaging biomarkers of therapy response. Purpose: To monitor the anti-angiogenic effects of a novel combination therapy on experimental head and neck squamous cell carcinomas (HNSCC) with dynamic contrast-enhanced (DCE)-MRI. Material and Methods: Athymic rats ( n  = 18) with subcutaneous HNSCC xenografts were investigated by DCE-MRI before and after 7 days of a daily triple therapy regimen combining the COX-II-inhibitor celecoxib, the matrix-metalloproteinase-inhibitor GM6001, and the uPA-inhibitor upamostat. Quantitative measurements of tumor blood flow (tBF), tumor blood volume (tBV), and permeability-surface area product (PS) were calculated and validated by immunohistochemistry. Results: Mean tBF and tBV in triple-therapy animals decreased significantly from day 0 to day 7 (tBF, 41.0 ± 14.2 to 20.4 ± 5.7 mL/100 mL/min; P  < 0.01; tBV, 17.7 ± 3.9 to 7.5 ± 3.3%; P  < 0.01). No significant effects on PS were observed in either group ( P  > 0.05). Immunohistochemical analysis showed a significantly lower tumor vascularity in the therapy group than in the control group (CD31), significantly fewer Ki-67+ proliferating tumor cells and significantly more Capase-3+ apoptotic tumor cells ( P  < 0.05). Significant ( P  < 0.05) correlations were observed between tBF/tBV and CD31 (tBF, r = 0.84; tBV, r = 0.70), tBV and Ki-67 (r = 0.62), as well as tBF and caspase-3 (r = −0.64). Conclusion: DCE-MRI may be a suitable tool for the non-invasive monitoring of the anti-vascular effects of this innovative triple therapy regimen with potential for clinical translation.